Electronic coherence transfer in photosynthetic complexes and its signatures in optical spectroscopy. Issue 2 (2008) - Mančal Mančal, Tomáš Tomáš; Valkunas Valkunas, Leonas Leonas; Read Read, Elizabeth L. Elizabeth L.; Engel Engel, Gregory S. Gregory S.; Calhoun Calhoun, Tessa R. Tessa R.; Fleming Fleming, Graham R. Graham R.
Abstract : Effects of electronic coherence transfer after photoexcitation of excitonic complexes and their manifestation in optical spectroscopy are discussed. A general excitonic model Hamiltonian is considered in detail to elucidate the origin of energy relaxation in excitonic complexes. We suggest that the second-order quantum master equation for the reduced density matrix of electronic degrees of freedom provides the most suitable theoretical framework for the study of coherence transfer in photosynthetic bacteriochlorophyll complexes. Temperature dependence of the absorption band maximum of a simple excitonic dimer is interpreted in terms of coherence transfer between two excited states. The role of reorganization energy of the transitions in the magnitude of the effect is discussed. A large reorganization energy difference between the two states is found to induce significant band shift. The predictions of the theory are compared to experimental measurements of the bacterial reaction center absorption spectra of Rhodobacter sphaeroides As an example of a time-dependent spectroscopic method sensitive to coherences and possibly to their transfer, we present recent two-dimensional photon echo measurements of energy relaxation in the so-called Fenna–Matthews–Olson complex of Chlorobium tepidum, where distinct oscillatory patters predicted to be signatures of electronic coherence have been observed.